Pengembangan Buku Cerita Pop Up Berbasis Multikultural Pendidikan Untuk Anak Usia Dini - Ika Sugiarti; Hariyanto; Sayati Budi Astuti Kurnia; Iklimahnatun Anggistiani; Subaeri; Khozzaimah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research aims to create a pop-up picture book based on multicultural education for early childhood. Through this picture book, children can understand multicultural education and get used to the diversity around them. In addition, this picture book teaches children how to behave around friends who have different customs and cultures from themselves. This development study refers to the 4-D development design steps. It includes (a) definition, (b) design, (c) development, and (d) dissemination. Before conducting product trials, validation tests were carried out on three experts. Data were collected by conducting observations which were carried out twice, namely before giving the book and after giving the book. Data analysis was carried out through the gain score of pre-test and post-test scores. The product trial was carried out in two stages, namely a limited test with 12 children and the main test with 31 children of PGRI Silo 01 Kindergarten. The results of the product feasibility assessment of product verification were 3.8 (very feasible) for media experts and 4 (very feasible) for material experts. The effectiveness of illustrated pop-up books in instilling an understanding of multicultural education in early childhood is determined based on the results of the pre-test score of 5.13 and the post-test score of 5.95. From this comparison, it can be concluded that the use of pop-up picture books based on multicultural education is effective in increasing children's understanding of multicultural education.